2010
DOI: 10.1590/s0103-51502010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de casos entre a mobilização neural e um programa de alongamento muscular em lombálgicos crônicos

Abstract: INTRODUÇÃO: A dor lombar, responsável por 50% das disfunções músculo-esqueléticas, é uma das principais, senão a mais frequente, causa de dor, incapacidade funcional e laborativa. OBJETIVOS: Avaliar os efeitos da mobilização neural e do alongamento na flexibilidade, no quadro álgico e nas atividades funcionais de sujeitos com dor lombar. METODOLOGIA: Foram realizadas 20 sessões de um programa de mobilização neural e de um programa de alongamento muscular com dois grupos distintos em sujeitos que apresentavam l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 5 publications
(4 reference statements)
1
17
0
4
Order By: Relevance
“…Participants were divided into two groups: an experimental group (EG), which was treated with the Santhiflex™ -PPR method; and a control group (CG), which was given a lecture on postural orientation after a first evaluation between March and July 2010. low back pain using trunk extensors strengthening exercises. In contrast, a comparative study has found a significant improvement in low back pain in a group of patients treated twice a week for ten weeks (20 sessions) with neural mobilization (23).…”
Section: Methodsmentioning
confidence: 88%
“…Participants were divided into two groups: an experimental group (EG), which was treated with the Santhiflex™ -PPR method; and a control group (CG), which was given a lecture on postural orientation after a first evaluation between March and July 2010. low back pain using trunk extensors strengthening exercises. In contrast, a comparative study has found a significant improvement in low back pain in a group of patients treated twice a week for ten weeks (20 sessions) with neural mobilization (23).…”
Section: Methodsmentioning
confidence: 88%
“…Machado and Bigolin (2010) (22) , demonstrated the efficacy of the technique to compare it with the stretching technique in patients with chronic LBP, where there was a greater technical efficiency as much flexibility as pain in these individuals.…”
Section: Santos and Domingues (2008)mentioning
confidence: 99%
“…A mobilização neural, utilizada tanto em animais, com compressão nervosa 8 , quanto em humanos 17 se apresenta como ferramenta útil para redução de dor e melhora funcional, sendo que Mallman et al 18 observaram prevenção de hipotrofia de sóleos de ratos Wistar submetidos à compressão por amarria…”
Section: Tibial Anteriorunclassified